Penerapan Metode Kata Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Siswa Kelas I SDN Babakan 04 Cilacap Jawa Tengah - Lestari, Anna Firda; Salahudin, Anas; Sofyan, Muhammad (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
This study aims to determine the application on the word method to the beginning reading ability of grade 1 students in the Indonesian language subject. This study applies the word method with the indicators used, namely reading letters, distinguishing initial sounds, reading meaningful words, and reading comprehension. This study uses a class action research method (CAR). Data collection techniques used are in the form of observation, tests, and documentation. The subjects of this study were 16 students in grade I SDN Babakan 04 who were in Babakan village, Karangpucung sub-district, Cilacap district. Based on the results of the study, it can be concluded that 1) Students' initial reading ability before the application of the word method was still in the very poor category with an average of 51.56 students' initial reading ability and 37.5% classical learning completeness percentage with the “Less Once”. 2) The results of students' initial reading ability after the application of the word method, from those before the application of the word method got an average of 51.56 with a percentage of 37.5% to 74.21 with a percentage of 81.25% after two cycles of using the method say.